Gallein potentiates isoniazid's ability to suppress Mycobacterium tuberculosis growth - Rijal, Ramesh; Gomer, Richard H. (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (Mtb), the bacterium that causes tuberculosis (TB), can be difficult to treat because of drug tolerance. Increased intracellular polyphosphate (polyP) in Mtb enhances tolerance to antibiotics, and capsular polyP in Neisseria gonorrhoeae potentiates resistance to antimicrobials. The mechanism by which bacteria utilize polyP to adapt to antimicrobial pressure is not known. In this study, we found that Mtb adapts to the TB frontline antibiotic isoniazid (INH) by enhancing the accumulation of cellular, extracellular, and cell surface polyP. Gallein, a broad-spectrum inhibitor of the polyphosphate kinase that synthesizes polyP, prevents this INH-induced increase in extracellular and cell surface polyP levels. Gallein and INH work synergistically to attenuate Mtb's ability to grow in in vitro culture and within human macrophages. Mtb when exposed to INH, and in the presence of INH, gallein inhibits cell envelope formation in most but not all Mtb cells. Metabolomics indicated that INH or gallein have a modest impact on levels of Mtb metabolites, but when used in combination, they significantly reduce levels of metabolites involved in cell envelope synthesis and amino acid, carbohydrate, and nucleoside metabolism, revealing a synergistic effect. These data suggest that gallein represents a promising avenue to potentiate the treatment of TB.